Radiosurgical treatment of cavernous sinus cavernous haemangiomas - (:unkn) unknown (SPRINGER WIEN, 2004)
Background. The objective of this report is to evaluate the effects of radiosurgery on cavernous sinus cavernous haemangiomas (CSCHs). Method. Five cases of CSCHs are presented in this report. One of them was diagnosed only neuroradiologically. Other patients underwent surgery and were then referred to Gamma Knife radiosurgery for residual tumours. The cohort consisted of 3 male and 2 female patients with median age of 42 (37-60). The volume of the tumours ranged between 3.8-6.5 cc. They were treated with a marginal dose of 14 to 16 Gy (mean 15 Gy). Findings. In the mean follow-up period of 32 months (6-52 months) all of the tumours decreased in size. There were no complications related to radiosurgery. Conclusion. Gamma Knife radiosurgery is an effective method in the treatment of CSCH, over the period of follow-up described.
Keywords: cavernoma; cavernous haemangioma; cavernous sinus; radiosurgery